An Electrophoretic Study of Natural Populations of the Cocoa Pod Borer, Canopomorpha cramerella (Snellen) from Malaysia - Muhamad Awang, Rita; Tan, Soon Guan; Gan, Yik Yuen; Sinha, Rita; Kanasar, Sivarogini; Asuan, K. (1989)
Cocoa pod borers from Tawau, Sabah and Sua Betong, Negeri Sembilan and rambutan fruit borers from Serdang and Puchong, Selangor and Kuala Kangsar, Perak, Malaysia were subjected to electrophoretic analysis in an effort to find diagnostic electromorphs between these two bio types of Conopomorpha cramerella. Thirty enzymes and general proteins were successfully demonstrated on zymograms but none of them could serve as diagnostic markers between cocoa pod borers and rambutan fruit borers. The allelic frequencies for 8 polymorphic enzymes are presented.